Prosthetic Rehabilitation of Patients with Maxillary Defects Post Mucormycosis: Case Series - Yadav, S; Abhinav, G (Journal of Nepalese Prosthodontic Society, 2022)
Mucormycosis has emerged as an epidemic within a pandemic of COVID 19 in India. It has emerged especially during second wave of COVID 19. Four major factors which are critical for the treatment of mucormycosis are rapidity of diagnosis, reversal of underlying predisposing factors (if possible), appropriate surgical debridement of infected tissue and appropriate antifungal therapy. Patient with maxillary resection present a challenging situation for the prosthodontist. Prosthetic rehabilitation is often difficult to achieve in such cases due to absence of many teeth and lack of favorable tissue undercuts. Obturator prosthesis should recreate the partition between oral and nasal cavities to restore oral function and esthetics. This case series presented the prosthodontic management of patients with hemimaxillectomy and premaxillary resection secondary to mucormycosis using maxillary interim obturator.